Generic symmetry analysis of charmonium decay - X.H. Mo (Physics Letters B)
For charmonium's decaying to the final states involving merely light quarks, in light of SU(3) flavor symmetry, a systematic parametrization scheme is established, which involving binary decays, ternary decays and radiative decays.